Rancang Bangun Sistem Pemesanan Jadwal Laundry Self Service Berbasis Website Menggunakan Protokol MQTT Rancang Bangun Sistem Pemesanan Jadwal Laundry Self Service Berbasis Website Menggunakan Protokol MQTT - Salma Febrila; Nugroho Suharto; Lis Diana Mustafa (Jurnal Jaringan Telekomunikasi, 2020)
In this study, customers had to queue in order to get their turn for laundry. So that users need a long time so it is less time efficient. This self-service laundry has a washing schedule booking service through the website making it easier for laundry service users without the need to queue. The method used in this study is an application for ordering laundry schedules via the website and an RFID tag as a card to access self-service laundry services. First, the user registers with customer service to get an RFID tag in the form of a smart card containing the user's identity and balance so that they can operate the washing machine. This research measures the accuracy of the weight sensor, the accuracy of the RFID distance, and the communication system between hardware and software. In the test results, the accuracy of the weight sensor obtained an error percentage of 0.28% to 1.69%. In testing the accuracy of the RFID distance, the reading of the RFID tag with a reader was obtained from a distance of 0 cm to 3 cm. In testing QoS (Quality of Service) using parameters delay, packet loss and throughput. In the delay test, the test results obtained are 0.057ms to 15.426ms. In the packet loss test it was obtained 0%. Whereas in the throughput test, the results obtained are around 0.337 Kbps to 6,758 Kbps.